A direct synthesis of atractylodinol, a potent inhibitor of PRRSV, and its biological evaluation. Issue 47 (23rd November 2016) - Kraus, George A.; Dong, Pengfei; Qu, Yang; Evans, Alyssa; Carpenter, Susan
Graphical abstract: Highlights: A synthesis of an inhibitor of the PRRS virus is described. Analogs were evaluated for viral inhibition. Analog8 shows excellent inhibition of the PRRS virus. Abstract: A direct synthesis of atractylodinol from 2-furylbutenyne and bromoacetylene6 is reported. Both compounds1 and8 showed greater than 99% virus inhibition.